Liza Colón-Zayas Likes 'Hacks' and Movie Scores. - BAHR, SARAH (New York Times, 2022)
The article features actress Liza Colón-Zayas and some of her favorites like the movie score of the film "The Ten Commandments," playwright Stephen Adly Guirgis, and the Labyrinth Theater Co.